THE INFLUENCE OF CRITICAL THINKING SKILLS, SELF CONFIDENCE, INDEPENDENT LEARNING, DIGITAL LEARNING, AND TEACHING SKILSS OF LECTURERS ON THE ACADEMIC ACHIEVEMENT OF STUDENTS IN THE ECONOMICS PROGRAM ECONOMICS EDUCATION, CLASS OF 2021 UNIVERSITY OF PGRI WES - Shafira, Herlina; Yosi Eka Putri; Meri Rahmania (Journal of Practice Learning and Educational Development, 2025)
This study aims to analyze 1) the effect of critical thinking skills on academic achievement, 2) the effect of self-confidence on academic achievement, 3) the effect of independent learning on academic achievement, 4) the effect of digital learning on academic achievement, 5) the effect of lecturers' teaching skills on academic achievement, (6) the combined influence of critical thinking skills, self-confidence, independent learning, digital learning, and lecturers' teaching skills on the academic achievement of students in the 2021 Economics Education Study Program at the University of Pgri West Sumatra. This research is descriptive and associative in nature. The population in this study was all students in the economics education program, totaling 110 samples. Sampling was conducted using the total sampling technique. The instrument used for this study was a closed questionnaire with a multiple linear regression test and hypothesis testing using t-tests and F-tests. The results of the study indicate that: First, critical thinking ability has a positive and significant effect on students' academic achievement, with a coefficient value of 0.013, a t-value of 21.389 > t-table 1.981, and a significance value of 0.000 < 0.05. Second, self-confidence has a positive and significant effect on students' academic achievement with a coefficient value of 0.002, a t-value of 2.158 > t-table 1.981, and a significance value of 0.033 < 0.05. Third, learning independence has a positive and significant effect on students' academic achievement with a coefficient value of 0.002, a t-value of 2.738 > t-table 1.981, and a significance value of 0.007 < 0.05. Fourth, digital learning has a positive and significant effect on students' academic achievement with a coefficient value of 0.001, a t-value of 2.465 > t-table 1.981, and a significance value of 0.0015 < 0.05. Fifth, the teaching ability of lecturers has a positive and significant effect on students' academic achievement with a coefficient value of 0.002, a t-value of 7.771 > t-table 1.981, and a significance value of 0.000 < 0.05. Sixth, collectively, critical thinking skills, self-confidence, independent learning, digital learning, and teaching ability of lecturers have a positive and significant effect on the academic achievement of students in the Economics Education Program, class of 2021, at the University of PGRI West Sumatra.